Layers of Protection: Smallpox, Contagion, and Community in Eighteenth-Century Boston. - Weir, Elise A. (Tufts Archival Research Center, 2015)
This thesis explores how Boston experienced and protected against smallpox outbreaks during the eighteenth century. It explores this from three levels: the government, the broader community, and the household. Boston developed a protective system through public health regulations and a community valuation of protecting the town and all its members. These measures challenged but never overturned traditional domestic healing.